Desain LinTar materi Daerahku dan Kekayaan Alamnya meningkatkan Adversity Quotient & Self Management Kelas IV SD Plus Sunan Pandanaran - N., Frika Trisetya; Fatih, Mohamad; Alfi, Cindya (Jurnal Simki Pedagogia, 2024)
The purpose of this study was to determine whether there was an increase in fourth grade students of SD Plus Sunan Pandanaran Blitar district regarding Adversity Quotient and Self Management skills. Research and Development (RnD) was used as the method in this study with waterfall as the model. Questionnaires, interviews and documentation were used to collect research data. Media, Material and Language experts acted as media validity testers. The assessment from the media expert scored 96.1% in the "Very Valid" category, 100% was obtained from the material expert and the linguist scored 97.7% in the same category. With a score of 92.5% the product was declared feasible by the class teacher. As for the increase in students' Adversity Quotient, it obtained an n-gain score of 0.9 in the "High" category as well as the results of increasing students' Self Management with a score of 0.8 in the "High" category. So it is concluded that Lintar media on the material of my region and its natural wealth is valid and able to increase the ability of Adversity Quotient and Self Management of fourth grade students of SD Plus Sunan Pandanaran.